Literature Review Impact of the Covid-19 Pandemic on Adolescent Mental Health - Ghozali Ghozali; Rusni Masnina; Sri Sunarti; Leni Mardiani; Denny Rivaldy; Lestiani Aulia Hasmy (Indonesian Journal of Global Health Research, 2021)
The Coronavirus Disease 2019 (COVID-19) pandemic experienced by almost all countries in the world has disrupted human life both economically, socially, and health itself. The danger posed by this disease in the form of a threat of death for sufferers as well as the very rapid nature of the disease transmission has consequences for the possibility of mental health problems, including in adolescents who are an age group that is vulnerable to change. The severity of the threat of disease and various prevention protocols that are legally enforced by the government can cause problems with anxiety, stress, depression, or trauma in adolescents. This study generally aims to examine the impact of the COVID-19 pandemic on the emergence of mental health problems in adolescents. The method used in this study is a literature review. The stages that will be carried out include determining the topic or problem that is the focus of the discussion, searching for references or literature relevant to the topic of discussion, reading, reviewing and analyzing the literature in accordance with the study objectives, as well as writing and describing the results of the review in the form of a narrative equipped with a summary in the form of a narrative. appropriate table form. Searches for relevant articles or references will be carried out on the online databases of Science Direct, Springer, Wiley Library, PubMed and Google Scholar. The keywords used to search for references are pandemic, COVID-19, mental health, anxiety, trauma, stress, and adolescent. The criteria for the year of publication of the literature are limited to a maximum two years (2019-2021) as the COVID-19 pandemic occurred since December 2019.